The bell ringers - Porter, Henry, 1953- (New York : Atlantic Monthly Press, 2009)
After her ex-boyfriend, a former head of intelligence, is killed, Kate Lockhart inherits his dangerous secrets, all having to do with the Orwellian reality this near-future England has become, and she soon finds herself on the run from the security-obsessed state.
Originally published: The dying light. London : Orion Books, 2009.
Keywords: Intelligence service -- Great Britain -- Fiction; Spy stories